Making Choices: A Multi-institutional, Longitudinal Cohort Study Assessing Changes in Treatment Outcome Valuation for Low-risk Thyroid Cancer - Antunez, Alexis G; Sinco, Brandy R; Saucke, Megan C; Bushaw, Kyle J; Jensen, Catherine B; Dream, Sophie; Fingeret, Abbey L; Livhits, Masha J; Mathur, Aarti; McDow, Alexandria; Roman, Sanziana A; Voils, Corrine I; et al. (Annals of surgery, 2025)
To evaluate the relative importance of treatment outcomes to patients with low-risk thyroid cancer (TC). Overuse of total thyroidectomy (TT) for low-risk TC is common. Emotions from a cancer diagnosis may lead patients to choose TT, resulting in outcomes that do not align with their preferences. Adults with clinically low-risk TC enrolled in a prospective, multi-institutional, longitudinal cohort study from November 2019 to June 2021. Participants rated treatment outcomes at the time of their surgical decision and again 9 months later by allocating 100 points among 10 outcomes. t tests and Hotelling T 2 statistic compared outcome valuation within and between subjects based on chosen extent of surgery (TT vs lobectomy). Of 177 eligible patients, 125 participated (70.6% response) and 114 completed the 9-month follow-up (91.2% retention). At the time of the treatment decision, patients choosing TT valued the risk of recurrence more than those choosing lobectomy and the need to take thyroid hormone less ( P <0.05). At repeat valuation, all patients assigned fewer points to cancer being removed and the impact of treatment on their voice and more points to energy levels ( P <0.05). The importance of the risk of recurrence increased for those who chose lobectomy and decreased for those choosing TT ( P <0.05). The relative importance of treatment outcomes changes for patients with low-risk TC once the outcome has been experienced to favor quality of life over emotion-related outcomes. Surgeons can use this information to discuss the potential for asthenia or changes in energy levels associated with total thyroidectomy.